Information Literacy in Nova Scotia: Systematic Mapping of High School Learning Outcomes - Munroe-Lynds, Cora-Lynn (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
<span data-sheets-value=""1":2,"2":"Information literacy has never been more important for the functioning of the democratic process, and for autonomy over one’s decisions. The Association for College and Research Libraries (ACRL) created a framework for information literacy, which lists six threshold concepts that an information literate individual possesses. This paper seeks to identify information literacy embedded in the Nova Scotia high school curriculum learning outcomes. Information literacy threshold concepts were mapped in the learning outcomes using qualitative coding. Findings from this study will reveal strengths and weaknesses in IL competencies in the Nova Scotia high school courses. This study also provides recommendation for future research."" data-sheets-userformat=""2":8961,"3":"1":0,"11":0,"12":0,"16":12">Information literacy has never been more important for the functioning of the democratic process, and for autonomy over one’s decisions. The Association for College and Research Libraries (ACRL) created a framework for information literacy, which lists six threshold concepts that an information literate individual possesses. This paper seeks to identify information literacy embedded in the Nova Scotia high school curriculum learning outcomes. Information literacy threshold concepts were mapped in the learning outcomes using qualitative coding. Findings from this study will reveal strengths and weaknesses in IL competencies in the Nova Scotia high school courses. This study also provides recommendation for future research.